Mythical Trickster Figures Contours, contexts and criticisms - Doty, William G.; Hynes, William J. (Tuscaloosa, London : The University of Alabama Press, 1993)
HYNES (W. J.) & DOTY (W. G.), Introducing the Fascinating and Perplexing Trickster Figure
DOTY (W. G.) & HYNES (W. J.), Historical Overview of Theoretical Issues : The problem of the trickster
HYNES (W. J.), Mapping the Characteristics of Mythic Tricksters : A heuristic guide
DOTY (W. G.), A Lifetime of Trouble-Making : Hermes as trickster
MAKARIUS (L.), The Myth of the Trickster : The necessary breaker of taboos
RICKETTS (M. L.), The Shaman and the Trickster
VECSEY (C.), The Exception who Proves the Rules : Ananse the Akan trickster
PELTON (R. D.), West African Tricksters : Web of purpose, danse of delight
ELLWOOD (R. S.), A Japanese Mythic Trickster Figure : Susa-no-o
HYNES (W. J.) & STEELE (T. J.), Saint Peter : Apostle transfigured into trickster
BEIDELMAN (T. O.), The Moral Imagination of the Kaguru : Some thoughts on tricksters, translation and comparative analysis
DOUEIHI (A.), Inhabiting the Space Between Discourse and Story in Trickster Narratives
HYNES (W. J.), Inconclusive Conclusions : Tricksters-metaplayers and revealers
TLS, 18/2/94, p. 28
bibliogr.